2006
DOI: 10.1590/s1516-35982006000500015
|View full text |Cite
|
Sign up to set email alerts
|

Efeito da composição do farelo de soja sobre o desempenho e o metabolismo de frangos de corte

Abstract: RESUMO -Foi estudado o efeito do teor de PB (44, 46 e 48%) do farelo de soja (FS) utilizado na composição das rações sobre o desempenho, o metabolismo e a micrometria intestinal de frangos de corte. Os três FS foram obtidos de um mesmo FS, com 48,4% PB, adicionado de níveis crescentes de casca de soja desativada. Foram utilizadas 312 aves, distribuídas em três tratamentos, com oito repetições. As rações formuladas para as três fases de crescimento (1 a 7, 8 a 21 e 22 a 42 dias) foram isocalóricas e isoprotéica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
2
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 2 publications
0
3
2
1
Order By: Relevance
“…The lipid content of soya meals (FSA and FSB) evaluated in this experiment were 4.01 and 5.82%, respectively, values higher than those were observed by Fernandes et al (2000); Mendes et al (2004); Gerber et al (2006) in soya meals. In most commercial soya meal described by other authors, the fat percentage is between 1.5 and 2.5%.…”
Section: Methodscontrasting
confidence: 61%
See 2 more Smart Citations
“…The lipid content of soya meals (FSA and FSB) evaluated in this experiment were 4.01 and 5.82%, respectively, values higher than those were observed by Fernandes et al (2000); Mendes et al (2004); Gerber et al (2006) in soya meals. In most commercial soya meal described by other authors, the fat percentage is between 1.5 and 2.5%.…”
Section: Methodscontrasting
confidence: 61%
“…The amounts of minerals in this research are about four times higher than those found in other studies (GERBER;JUNIOR;RIBEIRO, 2006;ZAMBOM et al, 2001;MENDES et al, 2004;FARIA et al, 2001;FERNANDES, RAM;SAKOMURA, 2000). It's important to remember the fact that soy meals of this study have been extruded, so mineral levels are considerably higher.…”
Section: Methodscontrasting
confidence: 54%
See 1 more Smart Citation
“…Similarly, Sakomura & Rostagno (2016) also observed different results from the ones in the present study, having reported an average ADCDM and ADCCP of 72.60% and 62.96%, respectively, while conducting studies using the excreta sampling method. However, when Gerber et al (2006) evaluated the digestibility of broilers from 39 to 42 days of age, using diets consisting of 46% corn and soybean meal, containing 3200 kcal/kg of ME; 19.12% of CP; 0.94% Lysine; 0.78% Met+Cys; they obtained similar results regarding the ADCGE (80.90%). However, their results differed in ADCDM (73.80%), due to lower dry material retention.…”
Section: Effects Of Nutritional Levels On Performance Carcass Characmentioning
confidence: 94%
“…Devido à polaridade do etanol, durante o processo de extração dos lipídios totais, pode arrastar outros compostos solúveis em solventes polares, como proteínas e minerais. Tanto a carne de frango e o farelo de soja, são ricos em proteína bruta e minerais, compostos solúveis em solventes polares (GERBER, 2006).…”
Section: Lotesunclassified